Electrical and GPR prospecting at Palo Blanco archaeological site, northwestern Argentina - Martino, Luis Angel (2006)
We conducted a geophysical survey at the Palo Blanco archaeological site located in Catamarca, Argentina. Age estimates from radiocarbon dating indicate first occupation of the site around 1500 years ago. The first description of thesite was done in 1960. At that time, five residential units with different architectural arrangements were reported. These structures had different levels of deterioration caused by exposure and human activities. Some of these original structures have become completely covered by sediments. To aid in the design of efficient excavation plans, detailed maps are required to locate the buried walls. For this purpose, we conducted geophysical surveys over one of the structures. We had poor documentation about the structure at the time of the survey. Only one of the walls described in the earlier report was partially visible. We used two geophysical methods: ground-penetrating radar (GPR) and electrical resistivity. We performed 2D inversion of the resistivity data, together with numerical GPR simulations. These helped to distinguish the expected reflection events from others, aiding in a correct interpretation of the data. Finally, we made a complementary interpretation of the resistivity and GPR data to compile a detailed map of the selected structure. We found that considering the two methods independently would have led to an incomplete map. We delineated a much more complex structure than originally expected and designed an excavation plan which was carried out. The layout of the rooms of the structure fully matched the predictions based on the interpretation used in detecting the walls and their depths. In this way, the geophysical forecasts were confirmed after excavation. © 2006 Society of Exploration Geophysicists.